側頭下顎障害患者におけるそしゃく運動経路の安定性の定量的評価 - SHIGA Hiroshi; KOBAYASHI Yoshinori; YOKOYAMA Masaoki; UNNO Mika; NAMBA Nerihisa (Journal of the Japanese Society for the Temporomandibular Joint, 2003)
In order to develop an objective evaluation for the stability of the masticatory movement path in patients with temporomandibular disorders (TMD), 20 healthy subjects and 20 TMD patients were asked to masticate three types of food with varying textures. A piece of chewing gum, one peanut, and a slice of crispy bread were used as test foods. The movement of the incisal point while masticating the test food for 10 seconds on the habitual side was recorded. Ten cycles beginning with the fifth cycle of mastication were analyzed. The stability of the masticatory movement path was determined by calculating the SD/OD (standard deviation/opening distance) of the opening lateral component, closing lateral component, and vertical component. All results were compared between the healthy subject group and the TMD patient group. The masticatory movement path of the healthy subject group was more stable than that of the TMD patient group for all test foods. There were significant differences between the two groups in the opening lateral component (gum: t=4.78, p<0.01, peanut: t=3.73, p<0.01, bread: t=2.60, p<0.05), closing lateral component (gum: t=4.37, p<0.01, peanut: t=2.61, p<0.05, bread: t=2.97, p<0.01), vertical component (gum: t=6.25, p<0.01, peanut: t=3.15, p<0.01, bread: t=2.57, p<0.05) respectively. These results confirmed that the masticatory movement path of TMD patients is less stable than that of healthy subjects. 側頭下顎障害 (TMD) 患者の咀嚼運動経路の安定性を客観的に評価する目的で, 20歳代の女性健常者20名 (健常群) と女性TMD患者20名 (TMD群) に主咀嚼側でチューインガム, ピーナッツ, 硬パンを咀嚼させ, 咀嚼開始後の第5サイクルからの10サイクルについて, 運動経路の安定性を表す開口時側方成分, 閉口時側方成分, 垂直成分のSD/OD (標準偏差/開口量) をそれぞれ算出後, 両群間で比較した。その結果, 開口時側方成分, 閉口時側方成分, 垂直成分のSD/ODは, いずれの食品咀嚼時でも, TMD群のほうが健常群よりも大きな値を示し, 開口時側方成分 (チューインガム咀嚼時: t=4.78, p<0.01, ピーナッツ咀嚼時: t=3.73, p<0.01, 硬パン咀嚼時: t=2.60, p<0.05), 閉口時側方成分 (チューインガム咀嚼時: t=4.37, p<0.01, ピーナッツ咀嚼時: t=2.61, p<0.05, 硬パン咀嚼時: t=2.97, p<0.01), 垂直成分 (チューインガム咀嚼時: t=6.25, p<0.01, ピーナッツ咀嚼時: t=3.15, p<0.01, 硬パン咀嚼時: t=2.57, p<0.05) のいずれにおいても両群間に有意差が認められた。これらのことから, TMD患者の咀嚼運動経路は, 不安定であることが確認された。